The effect of organic extracts on the microelements content in selected species of forage grasses - Milena Truba; Jacek Sosnowski; Krzysztof Pakuła (Journal of Water and Land Development)
The aim of the study was to determine the effect of soil fertilising biopreparations, i.e. compost extract, vermicompost extract and humus extract, used against the background of NPK mineral fertilisation, on the content of manganese, iron, zinc and copper in the biomass of Lolium perenne, Festulolium braunii, and Dactylis glomerata. In the spring of 2019 and 2020, a single dose of the biological preparation was applied. During each vegetation period, the plants were mown three times. During mowing, fresh plant mass was taken from each plot, dried, ground and the content of Cu, Zc, Mn and Fe was determined using the ICP-AES method. The use of a biological preparation with the composition of an extract from compost significantly increased the content of Mn, Fe and Zn in the dry mass of the tested grass species. The grass species that accumulated the highest total content of microelements in its above-ground parts was Lolium perenne. The use of only biological preparations in the cultivation of the analysed grass species gave better production effects, for example in the form of a higher concentration of microelements in the dry mass of plants compared to objects fed only with minerals. This creates the possibility of using the tested biopreparations in organic farms. The Fe:Mn ionic ratio was too wide in relation to the standards on all experimental objects, which resulted from the excess of Fe in the plants. Only the combination of compost extract with mineral fertilisation narrowed the above relationship, but it was still too high.